Acetone - Zinc Bromide as Working Fluids in Solar Absorption Cooling System - Ghyadh, Nabeel A.; Hammadi, Salman H.; Shahad, Haroun A. K. (Basrah Journal for Engineering Sciences, 2020)
This study presents both experimental and theoretical investigations of an absorption refrigeration system using environmentally friendly working fluids, specifically the acetone–zinc bromide (Acetone/ZnBr₂) pair. The system was designed to operate under outdoor climatic conditions in Hilla City, Iraq, utilizing hot water as the heat source. Performance evaluation was carried out under various operating conditions, including changes in heat source, absorber, condenser, and evaporator temperatures. Experimental testing was conducted during September 2019. The results indicated that the coefficient of performance (COP) of the absorption cooling system ranged from 0.13 to 0.487, with an evaporator temperature drop of approximately 16 °C. Condensation and absorption temperatures remained below 41 °C, while the maximum driving water temperature reached 80 °C. A steady-state theoretical model was developed using the Engineering Equation Solver (EES) program, applying mass and energy balance equations to predict operating parameters such as temperature, pressure, and COP. Model predictions showed good agreement with the experimental measurements. Furthermore, the results confirmed that generator temperature has a significant influence on overall system performance.